The current situation Chinese third-party logistics companies are facing - an exploratory study : 112.889 (120 credits) thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Science (MApplSc) in Logistics and Supply Chain Management at Massey University, Auckland, New Zealand - Liu, Yongli (Massey University, 2008)
The fast development of the Chinese economy has brought tremendous impact on the growth of logistics industry in the country. China has become the hottest market for both Chinese and foreign third-party logistics companies (3PL providers), and more and more foreign and domestic 3PL providers are being involved in the Chinese logistics industry. To understand the current situation Chinese third-party logistics companies are facing and the competitive strategies they are pursuing, an exploratory investigation was conducted in the study. A multiple case-study approach was adopted as the main strategy and guidance for the study. Under the principle of multiple case studies, multiple instruments (questionnaire, telephone interviews and archive searching) were used in the data collection among three selected case study companies. Also, within-case analysis and cross-case analysis were chosen as the overall framework of data analysis, and content analysis was selected as the main method for qualitative data analysis. Through investigating a variety of aspects of the three case study 3PL companies, the study has identified that all the case study companies have established country-wide logistics networks, have provided customers a range of logistics services, and have adopted different information technology systems in their operations. All the case study companies have achieved constant increase in their sales in recent years. Generally, the competition in the Chinese 3PL industry is fierce, and sometimes chaotic, unfair, and even illegal. Foreign 3PL providers have been considered as major competitor by Chinese 3PL providers. All the case study companies have developed and pursued a number of competitive strategies to gain competitive advantages in both cost and service. The main competitive strategies addressed include distribution network developing strategy, information technological strategy, and long-term partnership strategy.
Keywords: Case studies; Logistics networks; Business competition; Information technology; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management